Mechanisms of immune regulation and transplantation immunity in corneal transplants - V. V. Neroev; N. V. Balatskaya; E. V. Chentsova; Kh. M. Shamkhalova (Медицинская иммунология, 2020)
At the present time, corneal transplantation (keratoplasty) is one of the most frequent modes of solid tissue transplants in the world. Unlike other kinds of transplants, corneal grafting is often performed without tissue typing and systemic immunosuppression.High frequency of transparent corneal engraftment (up to 90% of cases) in the absence of risk factors is due to special immunoprivileged area in the anterior eye segment (functionally, a structural aggregation of the cornea and anterior chamber, AC) accomplished by local and systemic immunoregulatory mechanisms, i.e., phenomenon of immune deviation associated with anterior chamber of the eye (ACAID), components of the internal liquid medium, a watery moisture with immunosuppressive properties, e.g., IL-1ra, TSP-1,TGF-β2, regulatory complement proteins, α-MSH (alpha-melanocyte stimulating hormone), VIP (vasoactive intestinal peptide), indolamine 2,3-dioxygenase (IDO), calcitonin-gene-bound peptide (CGRP), somatostatin, etc.In addition to ACAID and liquid AC components, a contribution to the maintenance of immune privilege which is extremely important for a successful outcome of keratoplasty, is provided by other mechanisms, in particular, immunologically active membrane-associated molecules of corneal endothelium, i.e., PDL-1 (Programmed death ligand 1), and sVEGFR-1, sVEGFR-2, sVEGFR-3 involved in maintaining avascularity of the corneal tissue. Disturbances of the immune privilege of the cornea promotes activation of immune recognition with switching the effector mechanisms of transplantation immunity, thus leading to subsequent development of the tissue incompatibility reaction and clouding of transplanted cornea. Graft rejection can be localized in any of the corneal cell layers, including epithelium, stroma, and endothelium. Endothelial rejection causes the most severe affection of visual functions, due to the inability of local endothelial recovery, and water accumulation due to the endothelial dysfunction.Graft rejection is clinically characterized by edema and the presence of inflammatory cells, either circulating in the anterior chamber, or forming precipitates on the graft endothelial cells.A number of factors are associated with an increased risk of corneal graft rejection, including the degree of inflammation and/or vascularization of the transplant bed i.e., location of the donor cornea, repeated keratoplasty, allosensitization due to other cellular transplants, including bone marrow, blood transfusions, pregnancy, etc., as well as allergic and systemic diseases.This review article considers and systematizes the data from the literature concerning studies of the factors determining the immune privileged state of cornea, and the ACAID phenomenon, their role in development of allotolerance in corneal transplantation, highlights the main conditions required for triggering the tissue incompatibility reactions, discusses the mechanisms of allogeneic recognition and effector stage of the immune response, destruction of corneal allografts.